De la asistencia a la intervención social: el voluntariado en la construcción de agencias en escuela bilingüe - Saucedo Revollo Lage, Marisol Patricia; Coelho Liberali , Fernanda (Colombian Applied Linguistics Journal, 2022)
This study aimed to examine the agency construction process with students who participated in an educational volunteering program proposed at a bilingual Spanish and Portuguese school in the city of São Paulo. The results of the project are presented, which was carried based on two inquiries: What types of agencies are built in the course of educational volunteering? How are these agencies constructed? The corpus of analysis consisted of video and audio recordings, as well as written documents on the tasks carried out by the group. The data were analyzed according to enunciative, discursive, and multimodal categories, and this allowed analyzing the manifestations of contradictions, as well as the decision-making by the participants. The document analysis indicated that the meetings intensified the relationships among the members, and the achieved objectives allowed expanding the repertoire in the construction of criticalcollaborative activist, relational, non-encapsulated, and transformative agencies. In this way, it was possible to analyze the construction of new ways to act, which made it possible to (re)signify the life of society in school as well as that of school in society. This study also produced important reflections on protagonism and agency.